(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
The relevance of early learning a foreign language is dictated by the needs of society. The progressive development of interethnic ommunication in recent years necessitates teaching children a foreign language, especially English, starting from preschool age. At preschool age, when teaching English, the child, first of all, learns communication.